MANAJEMEN MODEL PEMBELAJARAN KOLABORATIF UNTUK MENINGKATKAN LITERASI MEMBACA (STUDI KASUS DI SDN 1 CIRIRIP) - Enjang Sarip Hidayat; Amelia Pratiwi; Wita Puspita Sari; Silvi Madya; R Supyan Sauri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the management of a collaborative learning model in improving reading literacy among fourth-grade elementary school students at SDN 1 Ciririp. The research employed a descriptive qualitative approach with emphasis on the POAC management functions: planning, organizing, actuating, and controlling. Data were collected through observation, interviews, and documentation involving the principal, fourth-grade teacher, and students. The findings reveal that planning involved determining learning objectives, preparing reading materials, and forming heterogeneous groups. Organizing was carried out through role distribution within groups. Actuating was implemented through shared reading, discussion, and presentation. Controlling was conducted through process and outcome evaluation. The collaborative learning model proved effective in improving student participation, reading comprehension, and confidence in expressing opinions.